Mechanical damage and failure mechanisms of chlorite by molecular dynamics - Li Liu; Xinlong Li; Runqing Zhang; Ran Ji; Wenhao He; Huaizhong Shi; Zhongwei Huang; Yongxin Li; Gaojian Fan; Songqing Zhao (Results in Engineering, 2025)
Chlorite schist, a layered soft rock with low strength and significant water-induced softening, poses challenges for deeply buried underground projects due to large deformations and collapse during excavation. To address the limited understanding of its deformation and failure mechanisms, especially at the microscopic level, this study employs molecular dynamics simulations to analyze the mechanical strength and deformation behavior of chlorite under varying loads and high-temperature conditions. Results reveal that chlorite exhibits anisotropy, with lower strength perpendicular to its molecular layers and higher resistance to compression compared to tension. Mechanical properties, including Young's modulus, shear modulus, and ultimate strength, decrease with increasing temperature. Failure mechanisms are dominated by the collapse and bending of clay mineral layers, influenced by loading paths and directions. Energy dissipation occurs through atomic pair positional changes, with van der Waals and Coulomb energies displaying opposite trends during tensile and compressive deformation. This study investigates the mechanical properties and deformation-failure mechanisms of the clay mineral chlorite, providing a theoretical foundation for further research on the large deformation and collapse of soft rock tunnels induced by temperature-fluid-mechanical coupling effects.